Crack initiation and propagation in small-scale yielding using a nonlocal GTN model. (July 2020) - Chen, Youbin; Lorentz, Eric; Besson, Jacques
Abstract: This study aims at investigating a non-local Gurson-Tvergaard-Needleman (GTN) ductile damage model at finite strains within the framework of small-scale yielding. This model solves the problems of spurious strain localization and volumetric locking. The model is applied to simulate large crack propagation under small-scale yielding and plane-strain mode I conditions. A new method to extract crack length from the porosity field is introduced. Besides, purely numerical parameters are introduced to help convergence. An adequate range is exhibited for each of them so that their impact on the J − Δ a crack growth resistance curves remains negligible. A parametric study is performed for several values of the material properties in order to estimate their influence on the crack growth resistance. It is found that the relation between the non-local intrinsic length implicitly introduced by the hardening gradient terms and the width of the damage/strain localization band is quasi-linear; crack tip blunting, crack initiation and large crack propagation can be well captured with the modified GTN model; the numerical formulation is robust; wide ranges for material plasticity and damage parameters can be used in a reliable way so that toughness at crack initiation as well as ductile tearing behavior can be thoroughly studied. Highlights: A nonlocal GTN model is proposed to solve the issues of spurious strain localization. A quasi-linear relationship between the non-local intrinsic length and the width of the damage/strain localization band is established. Crack tip blunting, crack initiation and large crack propagation can be well captured with the modified GTN model in the context of small-scale yielding. The numerical formulation is robust; wide ranges for the plasticity and damage parameters can be used in a reliable way.